Clinical and Histological changes after ridge preservation with two xenografts: preliminary results from a multicentre randomized controlled clinical trial. (10th January 2017) - Barone, Antonio; Toti, Paolo; Quaranta, Alessandro; Alfonsi, Fortunato; Cucchi, Alessandro; Negri, Bruno; Di Felice, Roberto; Marchionni, Saverio; Calvo‐Guirado, Jose' Luis; Covani, Ugo; Nannmark, Ulf
Abstract: Objectives: To evaluate and compare clinical and histological changes after ridge preservation procedures with those of spontaneous healing. Materials and Methods: Ninety patients were enrolled in the present randomized controlled clinical trial and underwent single‐tooth extraction in the premolar/molar areas. Thirty sites were grafted with collagenated cortico‐cancellous ( coll ), 30 sites with cortical ( cort ) porcine bone and 30 sites underwent natural healing. Primary (vertical and horizontal bone changes after 3 months) and secondary outcomes (histomorphometric after 3 months) were evaluated at implant placement. Results: The vertical bone changes at the grafted sockets were significantly ( p  < 0.0001) lower (0.30 mm for cort group and 0.57 mm for coll group) when compared to non‐grafted sockets (2.10 mm for nat group). Moreover, the width reduction of the coll (0.93 mm) and cort (1.33 mm) groups was significantly lower ( p  < 0.0001) than the non‐grafted group (3.60 mm). The analysis of subgroups attested that when premolar and molar sites were compared, the buccal bone loss appeared to be dependent both on tooth position and grafting material employed. Conclusion: The ridge preservation procedures had significantly better outcomes when compared to natural healing. The biomaterials did not differ for maintenance of bone width; even though, the bone height seemed to be better preserved with the cortical porcine bone.